2021
DOI: 10.1101/2021.07.06.21259528
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pre-vaccination and early B cell signatures predict antibody response to SARS-CoV-2 mRNA vaccine

Abstract: SARS-CoV-2 mRNA vaccines are highly effective, although weak antibody responses are seen in some individuals with correlates of immunity that remain poorly understood. Here we longitudinally dissected antibody, plasmablast, and memory B cell (MBC) responses to the two-dose Moderna mRNA vaccine in SARS-CoV-2-uninfected adults. Robust, coordinated IgA and IgG antibody responses were preceded by bursts of spike-specific plasmablasts after both doses, but earlier and more intensely after dose two. Distinct antigen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Kardava et al studied the response of B cells in the Moderna COVID-19 vaccine (mRNA-1273), showing a brief burst of this subpopulation on day seven post-vaccination followed by a slower phase studied until day 60 post-vaccination. 46 This elevation is consistent with the intergroup increase in our analysis; on the other hand, the decrease of this subpopulation in immunized individuals compared to CS could be due to the probable differentiation toward plasmablast and plasma cells, as this subset increases the expression of BLIMP-1 while maintaining the expression of Pax5 , two transcriptional factors involved in differentiation to plasma cells. 47 Complementary to the above, early plasmablasts have also been related to an extrafollicular response, being producers of IgM-type antibodies before a rapid response to antigen.…”
Section: Discussionsupporting
confidence: 89%
“…Kardava et al studied the response of B cells in the Moderna COVID-19 vaccine (mRNA-1273), showing a brief burst of this subpopulation on day seven post-vaccination followed by a slower phase studied until day 60 post-vaccination. 46 This elevation is consistent with the intergroup increase in our analysis; on the other hand, the decrease of this subpopulation in immunized individuals compared to CS could be due to the probable differentiation toward plasmablast and plasma cells, as this subset increases the expression of BLIMP-1 while maintaining the expression of Pax5 , two transcriptional factors involved in differentiation to plasma cells. 47 Complementary to the above, early plasmablasts have also been related to an extrafollicular response, being producers of IgM-type antibodies before a rapid response to antigen.…”
Section: Discussionsupporting
confidence: 89%
“…This inflammatory signature persisted postvaccination, and further analysis revealed that the genes in this high-responder signature were most closely linked to innate sensing of Gram-negative bacteria (lipopolysaccharide, LPS) and fungi (zymosan), supporting our hypothesis that prior exposure to microbes might directly and significantly shape the nature of future responses to infection and vaccination [9]. Prevaccination immune signatures (reviewed in [10]) that can be used to predict certain vaccine responses have been studied in many contexts, including influenza virus [11,12], hepatitis B virus (HBV) [13], and in recent preliminary data (in preprint) in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections [14].…”
Section: Highlightsmentioning
confidence: 52%
“…Importantly, trained immunity has been demonstrated to enhance immune responses in the context of vaccination, initially with Bacillus Calmette-Guérin (BCG) [66][67][68] and the diphtheria, tetanus and pertussis (DTP) vaccines 66 and more recently with the influenza vaccines 55 . Studies have been performed to identify pre-vaccination signatures that predict vaccine efficacy and outcome [69][70][71][72] . Other studies have linked microbiota, metabolism, epigenetics and trained immunity shedding insight into the links of these critical pathways [73][74][75][76] .…”
Section: Memory: It Is Not Just For T Cells and B Cells Anymorementioning
confidence: 99%